THE EFFECT OF INDUKTIVE LEARNING MODEL ON LEARNING OUTCOMES STUDENT IN SUBJECT MOMENTUM AND IMPULSE - Putri Alkhasmi Harahap; Abd Hakim S (Jurnal Pendidikan Fisika, 2019)
This study aims to determine the effect of induktive learning model  on learning outcomes student in subject momentum and impulse Class X second semester SMA Panca Budi Medan T.P  2017/2018. This research is a quasi experiment. The population in this study throughout the second semester class X  student of SMA Panca Budi Medan consists of ten classes. The research sample was determined by random cluster sampling. Class X MIA 2 as a class use induktive learning model and X MIA 3 use conventional learning. The instrument in this research is multiple choice test which consists of 20 items. Post-test results obtained with an average velue of 71,71 experimental class and control class 61,43. The results of t test th > tt  obtained  3,969 <1,997. There was a different result influence students' learning outcomes  using induktive learning model better of learning conventional in the subject momentum and impulse in class X SMA Panca Budi Medan T.P. 2017/2018